Idiopathic Exposed Bone Lesions of the Jaw - Božana Lončar Brzak; Vanja Vučićević Boras; Ana Kotarac Knežević; Mato Sušić; Sven Seiwerth; Dragana Gabrić (MDPI AG, 2019)
Introduction: Osteonecrosis of the jaw is defined as exposed bone in the oral cavity that does not heal longer than eight weeks after identification. The two most common predisposing factors for osteonecrosis of the jaw are medication-related and radiotherapy. Rarely, exposed bone in the maxillofacial region can occur due to other causes and represents a clinical and therapeutic challenge for the dentist because there is no universally accepted treatment protocol. Case presentation: We report a case of a patient with two idiopathic lesions of exposed bone which have healed after systemic antibiotic therapy, seven weeks after the first examination. Conclusion: Exposed bone lesions of the jaw are a rare entity and are poorly documented in the literature. It is necessary to exclude possible local or systemic contributing factors. Surgical and conservative therapy (antibiotics) are the treatment of choice.